2019
DOI: 10.1002/pc.25421
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, gas sensing, and electrical property evaluation of polyaniline/copper‐alumina nanocomposites

Abstract: A series of organic‐inorganic hybrid of polyaniline (PANI)/copper‐alumina (Cu‐Al2O3) nanocomposites were prepared by in situ polymerization technique. The structural, morphological and thermal properties of PANI with different contents of nano Cu‐Al2O3 were characterized by Fourier transform infrared spectroscopy (FTIR), X‐ray diffraction analysis (XRD), scanning electron microscopy (SEM), high‐resolution transmission electron microscope (HR‐TEM), differential scanning calorimetry (DSC), and thermogravimteric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“… 20 Bandgar et al 21 developed a flexible PANI/α-Fe 2 O 3 nanocomposite with high NH 3 gas selectivity. In previous research, 22,23 we found that PANI/Cu–Al 2 O 3 and PIN/Cu–Al 2 O 3 had excellent electrical, thermal and ammonia gas sensing properties. The synergistic interaction of Cu–Al 2 O 3 with the polar entity of a conducting polymer is the basis of their superior properties.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“… 20 Bandgar et al 21 developed a flexible PANI/α-Fe 2 O 3 nanocomposite with high NH 3 gas selectivity. In previous research, 22,23 we found that PANI/Cu–Al 2 O 3 and PIN/Cu–Al 2 O 3 had excellent electrical, thermal and ammonia gas sensing properties. The synergistic interaction of Cu–Al 2 O 3 with the polar entity of a conducting polymer is the basis of their superior properties.…”
Section: Introductionmentioning
confidence: 80%
“… 23 PANI- co -PIN/Cu–Al 2 O 3 has a stronger initial gas sensitivity response than PANI/Cu–Al 2 O 3 nanocomposites. 22 …”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] The GIL disk insulator is mainly made of epoxy resin composites doped with micro-Al 2 O 3 with a mass fraction of 60%, which has guaranteed the thermal, mechanical, and basic insulation requirements for the insulator. [5][6][7] However, the doping of Al 2 O 3 fillers has also reduced the surface insulation performance. Due to the obstruction of charge transport brought by filler Al 2 O 3 , the surface of the insulator would accumulate a large amount of net charge under longterm action of DC electric field, which would aggravate the distortion of surface electric field, thus to induce the accidents of flashover.…”
Section: Introductionmentioning
confidence: 99%
“…The flashover accident of the disk insulator can be the most severe one 1–4 . The GIL disk insulator is mainly made of epoxy resin composites doped with micro‐Al 2 O 3 with a mass fraction of 60%, which has guaranteed the thermal, mechanical, and basic insulation requirements for the insulator 5–7 . However, the doping of Al 2 O 3 fillers has also reduced the surface insulation performance.…”
Section: Introductionmentioning
confidence: 99%
“…[4] The doping of copper into alumina (Cu-Al 2 O 3 ) not only increases the compatibility of hybrid with the polymer matrix but also improved the conductivity, thermal stability, and corrosion resistance. [5] Natural rubber (NR) is a fascinating rubber product that is naturally available. It is extensively used in the fabrication of tires, adhesives, coatings, surgical gloves, health equipment, and vehicle accessories.…”
mentioning
confidence: 99%